REARING OF GREEN CATFISH (Mystus nemurus C.V) ECO-FRIENDLY WITH BIOFLOCS TECHNIQUES - Ringgi Desra Denesta; Iskandar Putra; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from June until July 2014 at LaboratoryAquaculture of Technology University of Riau. The purpose of this research wasto investigate growth of the green catfish with high stocking density in bioflocstechniques. This research using experimental method and completely randomdesign (RAL) with three treatment and three replications, three are P1 : stockingdensity of green catfish 300 fish/m3, P2 : stocking density of green catfish 400fish/m3, P3 : stocking density of green catfish 500 fish/m3. The result showed thatgreen catfish with high density in bioflocs techniques was not effectedsignificantly on absolute growth weight, absolute growth length, daily growthrate, survival rate and feed efficiency. But the best treatments in this research wasstocking density of fish 500 fish/m3, with high growth weight rate 5,06 g, lengthgrowth rate 3,65 cm, daily growth rate 4,40 %, survival rate 100 %, and feedefficiency lowers 17,48 %.Keyword : Green catfish, High density, Bioflocs technology